Quaternary deformation associated with the eastern uplift front of the Sierras de Velasco and Ambato, western Sierras Pampeanas - Casa, A.L. (2010)
Along the eastern front of the Sierra de Velasco and at the southern end of the Sierra de Ambato, western Sierras Pampeanas, have been found new evidences of Quaternary tectonic activity near La Rioja city. Observed evidences correspond to different reactivated sections of the faults that bound the mountain fronts, as well as to structures affecting the Quaternary deposits on the piedmont. The bounding faults of the Sierra de Velasco Oriental-front exhibit a NNE trend and WNW dip, while structures at the southernmost Ambato range are characterized by NE trend and NW dip. The neotectonic faults of the El Carrizal block are the result of the interference of both structural trends, resulting in a sector with higher structural complexity. The here described deformation show the persistence of a compressive regime during the Quaternary, with eastern to southeastern verging reverse faults. It is considering that these faults are driving the current uplift of the mountain ranges and constitute potential earthquake sources.